ANALISIS PENERAPAN KOMUNIKASI EFEKTIF DENGAN TEKNIK SBAR TERHADAP RESIKO INSIDEN KESELAMATAN PASIEN - Siska Novi Anggaraini; Leni Wijaya (LPPM STIKes Mitra Adiguna, 2026)
Effective communication is a critical component in the delivery of nursing care, particularly in efforts to maintain patient safety. One communication method thathas proven effective is the SBAR (Situation, Background, Assessment, Recommendation) technique. This technique assists nurses in conveying informationsystematically, thereby reducingthe potential for errors in servicedelivery. This studyaims to analyze the application of effective communication using the SBAR technique on the risk of patient safety incidents at Musi Medika Cendekia Hospital in Palembang. This study employed a quantitative research design with a descriptive survey approach and a cross-sectional design. The sampling technique used was non-probability sampling with a total sampling method, involving 47 nurses who met the inclusion and exclusion criteria. Data were analyzed using univariate and bivariate analysis with the Chi-Square test. The results indicated that the majority of patient safetyincident risks were in the low category, with 30 respondents (63.8%). The application of effective SBAR communication was predominantly in the good category, with 30 respondents (63.8%), yielding a p-value of 0.000 (p < 0.05). Therefore, it can be concluded that there is a significant relationship between the application of effective communication with the SBAR technique and the risk of patient safety incidents. The better the implementation of SBAR communication by nurses, the lower the risk of patient safety incidents. It is recommended that nurses continuously enhance their communication skills, especially with the SBAR technique, as part of the effort to uphold patient safety. Effective communication facilitates faster decision-making, reduceserrors, enhances the qualityof nursing care, and mitigates the risk of adverse events.